PERSEPSI MASYARAKAT DESA PINGGIRPAPAS KECAMATAN KALIANGET KABUPATEN SUMENEP TERHADAP PENGGUNAAN MCK - Rahmanto, Ach.Desmantri; Suyuti, Suyuti (Universitas 17 Agustus 1945 Surabaya, 2020)
AbstractThe low level of community welfare and poor environmental quality are almost the same problems for all settlements in rural areas. A bad environment can be identified by looking at the aspects that affect the quality of the shelter, such as clean water networks, drainage, solid waste, sanitary facilities, density and poverty levels. The purpose of this research is to find out people's perceptions and attitudes towards healthy lifestyles related to the use of good toilets. The data analysis technique was used to determine the relationship between variables using Chi-Square Test Analysis. It can be seen that from some of the question items used as variables in this study, there are no variables that have Asymp values. Sig. (2-tailed) <0.05 and it can be concluded that based on the answers from a number of respondents more variables are acceptable and it can be concluded that the respondents' answers relate to several aspects of the later use of the MCK. So from these answers it can be concluded that the respondents prefer the answer